Dinamika dan Identitas Pembelajaran Mata Kuliah Ulumul Qur’an di Institut Agama Islam Bakti Negara (IBN) Tegal - Tri Subhi (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
The article focuses on affirming the distinctiveness of Ulumul Qur'an course learning at Institut Agama Islam Bakti Negara (IBN) Tegal. Based on qualitative research and library research, the article presents several points on the above theme. First, lecturers who teach Ulumul Qur'an courses in eight undergraduate study programmes at IBN Tegal must be professional lecturers and doctors in the field of Ulumul Qur'an. Second, building a digital learning climate based on scientific authority. Lecturers must have scientific authority while being able to accommodate student diversity in learning Ulumul Qur'an. Lecturers must be able to deliver learning materials by positioning themselves as facilitators with a variety of methods based on student conditions but still within the learning objectives of Ulumul Qur'an. Third, based on the historical aspect of IBN Tegal which was founded based on the values of boarding school and technocracy, lecturers teaching Ulumul Qur'an courses must adhere to the tradition of strict scientific sanad as prevailing in Islamic boarding schools as well as responsive to the development of science and technology as the spirit of technocrats.